Amanda Labarca Huberston: current legacy of an extraordinary teacher - Huaiquián Billeke, Claudia Andrea (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2018)
The aim of this paper is to reconstruct the personal, intellectual, and social trajectory of Amanda Labarca Huberston, one of the pioneers in the field of university teaching, devoted to the Chilean and Latin American schoolteaching. She was an outstanding political activist and fighter for universal suffrage, as well as for the rights of women. With this theoretical documentary analysis I intend to understand the biographical situation and the pedagogical proposal of Amanda Labarca. The method used was qualitative-descriptive, with a historiographic design developed with the methodological triangulation of primary and secondary sources. The results of this work may raise interest in an unexplored field of educational research in Chile: the life histories of Chilean teachers.